The centrifugal track as a tool for sprint-specific strength training (2016)
The centrifugal track has proven to be a valid alternative to common resisted sprint running techniques for sprint-specific strength training. Contrary to common resisted sprint running, running on a centrifugal track showed to provide a training effect without localized overloads on the musuloskeletal system and detrimental postural changes. Furthermore, conversely to sled towing, the centrifugal track allows to increase the overload without necessarily disrupting running kinematics. Longitudinal studies are needed to prove the benefits of the centrifugal track on sprint performance. Strength and conditioning researchers should also focus on the definition of ad-hoc training programs that may standardize the use and periodization of such a sprint-specific strength training tool.